Correlation of biomechanics and cancer cell phenotype by combined Brillouin and Raman spectroscopy of U87-MG glioblastoma cells - Rix, Jan; Uckermann, Ortrud; Kirsche, Katrin; Schmitz-Schackert, Gabriele; Koch, Edmund; Kirsch, Matthias; Galli, Roberta (Interface, 2022)
The elucidation of biomechanics furthers our understanding of brain tumour biology. Brillouin spectroscopy is a new optical method that addresses viscoelastic properties down to subcellular resolution in a contact-free manner. Moreover, it can be combined with Raman spectroscopy to obtain co-localized biochemical information. Here, we applied co-registered Brillouin and Raman spectroscopy to U87-MG human glioblastoma cells in vitro. Using two-dimensional and three-dimensional cultures, we related biomechanical properties to local biochemical composition at the subcellular level, as well as the cell phenotype. Brillouin and Raman mapping of adherent cells showed that the nucleus and nucleoli are stiffer than the perinuclear region and the cytoplasm. The biomechanics of the cell cytoplasm is affected by culturing conditions, i.e. cells grown as spheroids are stiffer than adherent cells. Inside the spheroids, the presence of lipid droplets as assessed by Raman spectroscopy revealed higher Brillouin shifts that are not related to a local increase in stiffness, but are due to a higher refractive index combined with a lower mass density. This highlights the importance of locally defined biochemical reference data for a correct interpretation of the Brillouin shift of cells and tissues in future studies investigating the biomechanics of brain tumour models by Brillouin spectroscopy.